In silico design and mechanistic study of niosome-encapsulated curcumin against multidrug-resistant Staphylococcus aureus biofilms - Khaleghian, Mohammad; Sahrayi, Hamidreza; Hafezi, Yousef; Mirshafeeyan, Mahshad; Moghaddam, Zahra Salehi; Farasati Far, Bahareh; Noorbazargan, Hassan; Mirzaie, Amir; Ren, Qun (Frontiers in Microbiology, 2023)
Curcumin, an important natural component of turmeric, has been known for a long time for its antimicrobial properties. This study aimed to investigate the anti-biofilm action of the niosomeencapsulated curcumin and explore the involved anti-biofilm mechanism. In-silico investigations of ADME-Tox (absorption, distribution, metabolism, excretion, toxicity) were first performed to predict the suitability of curcumin for pharmaceutical application. Curcumin showed low toxicity but at the same time low solubility and low stability, which in turn might reduce its antimicrobial activity. To overcome these intrinsic limitations, curcumin was encapsulated using a biocompatible niosome system, and an encapsulation efficiency of 97% was achieved. The synthesized curcumincontaining niosomes had a spherical morphology with an average diameter of 178 nm. The niosomal curcumin was capable of reducing multi-drug resistant (MDR) Staphylococcus aureus biofilm by 2-4-fold, compared to the free curcumin. The encapsulated curcumin also demonstrated no significant cytotoxicity on the human foreskin fibroblasts. To understand the interaction of curcumin and S. aureus biofilm, several biofilm-related genes were analyzed for their expression. Nacetylglucosaminyl transferase (IcaD), a protein involved in the production of polysaccharide intercellular adhesion and known to play a function in biofilm development, was found to be downregulated by niosomal curcumin and showed high binding affinity (-8.3 kcal/mol) with curcumin based on molecular docking analysis. Our work suggests that the niosome-encapsulated curcumin is a promising approach for the treatment of MDR S. aureus biofilm, and can be extended to biofilms caused by other pathogens.